The Effectiveness of Using Think-Aloud Strategy to Improve Students’ Reading Comprehension Ability in Recount Text at The Eighth Grade Students Of SMP N 3 Gombong in The Academic Year of 2015/2016 - Pratiwi , Hani Fatma (Scripta : English Department Journal, 2019)
The objective of the study is to describe the effectiveness of using think-aloud strategy to teach reading recount text to the eighth grade students of SMP N 3 Gombong. The subject of the study is the eighth grade students of SMP N 3 Gombong in the academic year 2015/2016. In this research, the researcher took 64 students of VIII C and VIII A as sample; they are experimental and control class. The result of the study showed that the students’ progress of experimental group in mastering reading ability is really good. It was found the result of t-value was 4.89. Based on the 0.05 significant level, the value of t-table was 1.68. The computation showed that t- value was higher than t-table, which was 4.89>1.68. Moreover, the mean of control class (71.38) is included into interval 70-79. It means that students of control class have good result on their reading ability. The mean of experimental class (77.13) is included into interval 70-79. It means that students of experimental class have good result on their reading ability. It shows that using think-aloud strategy on the teaching-learning process gives a positive contribution toward the students’ reading ability. So, the use of Think-Aloud Strategy was effective to improve students reading ability in recount text to eighth grade of SMP N 3 Gombong in Academic Year 2015/2016.